Borderlands Epistemologies and the Transnational Experience - Petrón, Mary A.; Greybeck, Barbara (GIST – Education and Learning Research Journal, 2014)
This reflective article is based on an ethnographic case study of five transnational teachers of English in Mexico. These teachers had acquired English as children of Mexican immigrants to the U.S. At the time of the study, they were living and teaching in their parents’ place of origin in rural Mexico. The intent of the article is to examine how borderlands ways of knowing were reflected in their personal and professional lives. The transnational experiences of living in and between nation states appeared at the forefront of their cultural and linguistic practices. They spoke the languages of transnationalism in that they engaged in translanguaging and considered English to be part of their heritage, too. They strongly identified with other transnationals who had similar backgrounds, and as teachers of English, they transformed their classroom into authentic lessons on language and culture. Their borderlands ways of knowing informed their linguistic identity and teaching practices.